Group Activity to Enhance Student Collaboration, Graph Interpretation, and Peer Evaluation of Ecological Concepts in a Large-Enrollment Class - Marcia A. Shofner (American Society for Microbiology, 2017)
This study presents an example for an activity that was implemented in a large enrollment (Principles of Ecology and Evolution) class to enhance student collaboration and critical thinking (e.g., graph interpretation and peer evaluation). In Spring 2015, a course redesign was initiated to move from teacher-centered to student-centered learning. We implemented six learning activities that each replaced one lecture. Here we will elaborate on two activities, McArthur and Wilson’s Island Biogeography Theory and Pikas and Climate Change. Both activities require students to use skills such as graph development and interpretation and quantitative reasoning. Students were divided into small groups and worked collaboratively on worksheets. Upon completion of the worksheet, each group was asked to exchange their worksheet with another group. Students were given ten minutes to review and comment on the other group’s worksheet answers. They recorded their comments (positive and negative feedback) directly on the worksheet and handed this back to the original group. The group activity and peer evaluation exercise offered were positively perceived by most of the students. Through the activities students learned about the process of scientific research, including formulating hypotheses, working collaboratively, reviewing each others’ work, being reviewed by others, and learning that there can be more than one way to interpret a graph.